'AnthropOcean': Oceanic perspectives and cephalopodic imaginaries moving beyond land-centric ecologies. (September 2018) - Brugidou, Jeremie; Fabien, Clouette
We sought contributions from the widest possible spectrum, asking the authors to reflect upon the notion of 'AnthropOcean': theory, fiction, journal, ethological accounts, or ethnographic material from time spent at sea, testimony by those who have gained experience from the ocean, encounters with ocean inhabitants (no species preferred), etc. The aim is to build imagination and sensitivity upon these contributions in order to invent new narrative forms coherent with our contemporary experiences of an animated world. We would like to suggest that oceanic sensitive-anthropology can provide precious sense-ideas in order to think, feel and imagine the contemporary ecological crisis. Considering our present as anything but an 'end of the world', and more as a profound transformative process, how can ocean-sense-ideas bring useful intuitions? How can ocean inhabitants, ecosystems and dynamics, teach us a lesson in imagination? Can we dream other dreams than that of industrial exploitation?